Microwave-Based Colonoscopy: Preclinical Evaluation in an Ex Vivo Human Colon Model - Glòria Fernández-Esparrach; Alejandra Garrido; Roberto Sont; Walid Dghoughi; Sergi Marcoval; Miriam Cuatrecasas; Sandra López-Prades; F. Borja de Lacy; María Pellisé; Ignasi Belda; Marta Guardiola (Gastroenterology Research and Practice)
Introduction. Microwave imaging can obtain 360° anatomical and functional images of the colon representing the existing contrast in dielectric properties between different tissues. Microwaves are safe (nonionizing) and have the potential of reducing the visualization problems of conventional colonoscopy. This study assessed the efficacy of a microwave-based colonoscopy device to detect neoplastic lesions in an ex vivo human colon model. Methods. Fresh surgically excised colorectal specimens containing cancer or polyps were fixed to a 3D positioning system, and the accessory device was introduced horizontally inside the ex vivo colon lumen and moved along it simulating a real colonoscopy exploration. Measurements of the colon were taken every 4 mm with the microwave-based colonoscopy device and processed with a microwave imaging algorithm. Results. 14 ex vivo human colorectal specimens with carcinomas (n=11) or adenomas with high grade dysplasia (n=3) were examined with a microwave-based device. Using a detection threshold of 2.79 for the dielectric property contrast, all lesions were detected without false positives or false negatives. Conclusions. This study demonstrates the use of a microwave-based device to be used as an accessory of a standard colonoscope to detect neoplastic lesions in surgically excised colorectal specimens.